Persepsi Mahasiswa PGSD Tentang Penggunaan Aplikasi Wordwall Dalam Mata Kuliah Pembelajaran Matematika SD - Rince S. M Benu; Adam Bol Nifu; Dyen E. Lakapu (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The perception of mathematics is difficult, boring and uninteresting experienced by PGSD students at the previous level. Of course, this has a negative impact on PGSD students participating in elementary mathematics learning courses. The purpose of this study is to find out students' perceptions of the use of word wall applications in elementary mathematics learning courses. The method used in this study is qualitative through a questionnaire using a google form. The results of the study show that students have a positive perspective in elementary mathematics learning courses because they use word walls. This can be seen in the percentage of 94.00% of students who revealed that the use of word wall applications is effective in making online games in elementary mathematics learning courses. As many as 94% stated that the template design in the word wall application attracted students' attention in making online games in elementary mathematics learning courses. A total of 87.88% revealed that the use of colors and fonts provided by the word wall application attracted attention and 93.94% stated that the use of word wall applications could increase motivation in elementary mathematics learning courses.